2018
DOI: 10.4103/jlp.jlp_26_18
|View full text |Cite
|
Sign up to set email alerts
|

Concept and connotation of oxidative stress in preeclampsia

Abstract: BACKGROUND:Preeclampsia (PE) is a systemic pregnancy-related disorder characterized by hypertension, proteinuria, and edema. Free radicals seem to play an important role in the induction of endothelial dysfunction in PE.AIM:The aim of the present study was to investigate serum levels of nitric oxide (NO), peroxynitrite (ONOO−), paraoxonase (PON-1), malondialdehyde (MDA), and lipid profile in preeclamptic patients compared to the women with normal pregnancy.MATERIALS AND METHODS:A total of 68 pregnant women wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…This finding confirms the role of free radicals in DIC. Increase in MDA level could be attributed to the effects of free radicals that are generated as a result of doxorubicin effect, on NADH-dependent microsomal LPO that initiates lipid radical chain and oxidative damage [18,19]. Also, pre-treatment with febuxostat led to significant decrease in MDA serum level compared to doxorubicin treated rats which coincided with a study that demonstrated a significant decrease in MDA serum levels during febuxostat treatment [20].…”
Section: Discussionsupporting
confidence: 55%
“…This finding confirms the role of free radicals in DIC. Increase in MDA level could be attributed to the effects of free radicals that are generated as a result of doxorubicin effect, on NADH-dependent microsomal LPO that initiates lipid radical chain and oxidative damage [18,19]. Also, pre-treatment with febuxostat led to significant decrease in MDA serum level compared to doxorubicin treated rats which coincided with a study that demonstrated a significant decrease in MDA serum levels during febuxostat treatment [20].…”
Section: Discussionsupporting
confidence: 55%
“…Pomegranate effect on free radicals is happened by different mechanism, it scavenges various types of free radicals such as ROS and reactive nitrogen species, and also, it inhibits ROS-generating enzymes including cyclooxygenase, lipoxygenase, and xanthine hydrogenase/ oxidase [6].…”
Section: Introductionmentioning
confidence: 99%
“…OCT4 was positive in 80% of Group A and 3.3% in Group B, in concomitant to Chinese study (2007) conducted on 49 bladder cancer biopsy samples and found that 40 of 49 bladder cancer samples (81.6%) showed the expression of OCT-4 of cancer cells [13]. In comparison to another study conducted in Iran (2007), a higher results observed as they detected the expression of OCT4 in almost all 96% of the examined tumor samples of bladder (31/32) 33% of Group C samples (3/9 of those without carcinoma) (Atlasi et al, 2007), and in Iran 2009, on 140 patients with bladder carcinoma, as noticed that among 140 cases, 9 (6%) cases showed no immunoreactivity for the OCT4 protein, whereas 131 (94%) cases showed positive immunoreactivity with a variety of intensities [14]. Lower results conducted in Egypt at 2017 on 84 urothelial tumor specimens, and found, of all the tumor specimens, 30 (35.8%) cases showed tumor positivity, whereas 54 (64.2%) cases were negative for OCT4 staining, in which all positive results found in high-grade urothelial tumor specimens [15].…”
Section: Discussionmentioning
confidence: 82%